2017
DOI: 10.1111/apt.14387
|View full text |Cite
|
Sign up to set email alerts
|

The taxonomic composition of the donor intestinal microbiota is a major factor influencing the efficacy of faecal microbiota transplantation in therapy refractory ulcerative colitis

Abstract: SummaryBackgroundFaecal microbiota transplantation is an experimental approach for the treatment of patients with ulcerative colitis. Although there is growing evidence that faecal microbiota transplantation is effective in this disease, factors affecting its response are unknown.AimsTo establish a faecal microbiota transplantation treatment protocol in ulcerative colitis patients, and to investigate which patient or donor factors are responsible for the treatment success.MethodsThis is an open controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
186
5
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(208 citation statements)
references
References 51 publications
7
186
5
10
Order By: Relevance
“…We were able to recapitulate major findings from all studies. For example, we identified disease-specific alterations in multiple studies in Akkermansia 39,31 24,40,39,33,20 and Streptococcus 34 (Fig. 2).…”
Section: Autoimmunity-associated Changes In Microbial Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to recapitulate major findings from all studies. For example, we identified disease-specific alterations in multiple studies in Akkermansia 39,31 24,40,39,33,20 and Streptococcus 34 (Fig. 2).…”
Section: Autoimmunity-associated Changes In Microbial Compositionmentioning
confidence: 99%
“…Following quality control (QC) and filtering, 20 16S rRNA studies remained for downstream analysis (Fig. 1) 19,20,[22][23][24][26][27][28]30,31,[33][34][35][36][37][38][39][40]46,47 . Notably, 8 out of the 20 studies used investigated the role of the human gut microbiome in IBD, due in part to its relatively high prevalence in 1.3% of US adults 48 .…”
Section: Autoimmunity-associated Changes In Microbial Compositionmentioning
confidence: 99%
“…The more abundant the donor microflora are, or to some certain bacteria are, the greater the symptom alleviation via FMT in patients with UC. Targeted therapy through specifically designed microbial agents may be a new approach to the treatment of UC . Brace et al analyzed microbial composition in patients with UC and CDI after treatment with multiple FMT and found that the degree of symptom relief was related to the patient's recovery because of the donor microbiota.…”
Section: Therapeutic Strategy Of Fmt In Uc and Controversymentioning
confidence: 99%
“…Targeted therapy through specifically designed microbial agents may be a new approach to the treatment of UC. 148 Brace et al 149…”
Section: Donor Selection In Fmtmentioning
confidence: 99%
“…Another potential application is pouchitis [89, 90]. During these studies, a number of mediators of treatment success were identified, among them the donor, the route of administration of the stool transplant, and others [91, 92]. …”
Section: Fmt In Fbdmentioning
confidence: 99%